2021
DOI: 10.7759/cureus.20859
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Resistance Patterns of Pediatric Urinary Tract Infections in Bahrain

Abstract: BackgroundUrinary tract infections (UTI) are a commonly encountered infection in the pediatric age group. Knowledge of the causative pathogens and their antimicrobial resistance patterns in specific geographical locations is important to provide optimum care. The aim of this study is to describe the prevalence and the antimicrobial resistance patterns of the pathogens causing UTI in the pediatric age group in one tertiary inpatient Pediatric unit in Bahrain. MethodsThis is a retrospective cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 28 publications
(79 reference statements)
2
13
0
Order By: Relevance
“…The current study confirmed earlier research that females were infected with E. coli at a greater incidence (48.0%) than males (38.2%) [ 19 ]. Only Pseudomonas was more prevalent in males than in females.…”
Section: Discussionsupporting
confidence: 92%
“…The current study confirmed earlier research that females were infected with E. coli at a greater incidence (48.0%) than males (38.2%) [ 19 ]. Only Pseudomonas was more prevalent in males than in females.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the ESBL E. coli had shown 100% resistance to cefotaxime and ceftazidime, similarly, the study was conducted by Al-Agamy et al and Kabrah found 100% resistance to the same drugs by the ESBL E. coli [36,37]. High -medium resistance rates (97.5% -46.5%) were detected to 11 resistance to the same drugs in their studies [38][39][40][41][42]. Lower resistance rate to gentamycin (14.7%), tobramycin (12.7%), least resistance to cefoxitin (7.6%) and 100% sensitivity to 8 different antibiotics which are mentioned in Table 4.…”
Section: Discussionsupporting
confidence: 82%
“…Interestingly, our statistical results showed that Egyptian infants (less than one year) were equally susceptible to E. coli and Klebsiella spp (36% and 38%, respectively). In contrast, there was a significant difference between the percentage of E. coli (68.6% out of 242 samples) and Klebsiella spp (10.3% out of 242 samples) in urine samples of infected Bahrani infants [ 5 ]. This difference may be due to different research designs, environmental conditions, or patient selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The most common UTI complications, such as proteinuria, high blood pressure, and kidney damage, can all come from a lack of renal function [ 4 ]. Female contraception use, personal hygiene issues, white ethnicity, a past previous UTI, a lack of water intake, neurological bladder disease, having diabetes, genitourinary instruments, being born with genitourinary abnormalities, phimosis, incomplete/infrequent urination, and prolonged constipation are all risk factors for UTI [ 5 ]. Gram-negative pathogens such as E. coli and Klebsiella spp are responsible for most UTIs [ 6 ].…”
Section: Introductionmentioning
confidence: 99%